Estimation of stochastic volatility models via auxiliary particles filter - Trosel, Yeniree (2019)
The growing interest in the study of volatility for series of financial instruments leads us to propose a methodology based on the versatility of the Sequential Monte Carlo (SMC) methods for the estimation of the states of the general stochastic volatility model (GSVM). In this paper, we proposed a methodology based on the state space structure applying filtering techniques such as the auxiliary particles filter for estimating the underlying volatility of the system. Additionally, we proposed to use a Markov chain Monte Carlo (MCMC ) algorithm, such as is the Gibbs sampler for the estimation of the parameters. The methodology is illustrated through a series of returns of simulated data, and the series of returns corresponding to the Standard and Poor’s 500 price index (S&P 500) for the period 1995 − 2003. The results show that the proposed methodology allows to adequately explain the dynamics of volatility when there is an asymmetric response of this to a shock of a different sign, concluding that abruptchanges in returns correspond to high values in volatility.